Rapid-maxillary-expansion induced rhinological effects: a retrospective multicenter study - (:unkn) unknown (SPRINGER, 2016)
Conventional dental-borne rapid maxillary expansion (RME) leads to a widening of the airways, followed by improved nasal breathing. Although combined skeletal-dental appliances are nowadays being inserted increasingly often and provide a force at the center of resistance in the nasomaxillary complex, no study exists so far that shows whether this treatment may improve the expansionary effect on the airways. In this study, low-dose computed tomography (CT) images from 31 patients (average age 14.63 +/- 0.38 years) were examined retrospectively. Both records (T0 = before expansion and T1 = immediately after maximum expansion) were taken in a time interval of 25 days to avoid growth influence. Five patients were treated with Hyrax RME, 6 patients with Hybrid RME, and 20 patients with acrylic cap RME. The total airway volume increased highly significantly (mean +/- 7272.6 mm 3; P < 0.001, power = 0.998), representing an average airway expansion of + 11.54 % (2.35 %/mm activation). While the nasopharynx and oropharynx showed highly significant expansion (P < 0.000, power = 0.999), the airway at the laryngopharynx did not change significantly (P > 0.779, power = 0.05). Although the patients were significantly older in the Hybrid RME group (P = 0.006), the positive rhinological effects were comparable within all groups of different appliances (P > 0.316). Hybrid RME may, therefore, be an advisable procedure in patients with nasomaxillary impairment and pronounced patient's age.
Keywords: Rapid maxillary expansion; RME; Hybrid RME; Airway expansion; Orthodontic interdisciplinary treatment; NASAL AIRWAY; 3-DIMENSIONAL ANALYSIS; CBCT DEVICES; DOSIMETRY; CT